1978
DOI: 10.1007/bf02125498
|View full text |Cite
|
Sign up to set email alerts
|

Course of coxsackie B antibodies during juvenile diabetes

Abstract: Sera of 83 patients with insulin-dependent diabetes of early onset were tested for latex agglutination-inhibiting antibodies to coxsackie virus types B1-B5. We could not find any evidence of a causal association between Coxsackie B virus infection and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…In all 26 studies were identified, all of which were case‐control studies. Of these 22 were full papers [5,13–31] (the paper by Banatvala et al . [23] contains three studies) and four were published as letters [12,32–34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all 26 studies were identified, all of which were case‐control studies. Of these 22 were full papers [5,13–31] (the paper by Banatvala et al . [23] contains three studies) and four were published as letters [12,32–34].…”
Section: Resultsmentioning
confidence: 99%
“…In all 26 studies were identified, all of which were case-control studies. Of these 22 were full papers [5,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (the paper by Banatvala et al [23] contains three studies) and four were published as letters [12,[32][33][34]. Figures for the study by Hadden [32] were obtained partly from a published letter by Gamble and Taylor [35].…”
Section: Resultsmentioning
confidence: 99%
“…coxsackie viruses and/or a greater frequency of positive serotests for several enteroviruses when comparing cases and control subjects [5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Several of the 'negative' studies deserve comment.…”
Section: For Debatementioning
confidence: 99%
“…Several of the 'negative' studies deserve comment. The Irish study [9] included non-insulin-dependent diabetic patients among its 'cases'.Two German studies [12,17] had no control subjects and concluded that coxsackie viruses could not be the aetiologic agent because they could not find evidence of infection in 100 % of cases. Another study tested for antibodies to only three coxsackie serotypes out of 67 known distinct serotypes of enteroviruses [13].…”
Section: For Debatementioning
confidence: 99%
See 1 more Smart Citation